The Impact of High-Speed Railway Accession on Agricultural Exports: Evidence from Chinese Agriculture-Related Enterprises. (13th August 2021) - Zhou, Jianjun; Fan, Xiayang; Yu, Aizhi
Abstract : Although many studies have analyzed the transportation infrastructure effects on economic and trade development, little is known about the relationship between transportation infrastructure and trade in the agricultural sector. We take the opening of China's high-speed railway (HSR) as a quasi-natural experiment and use multiperiod DID model to explore the impact and mechanism of HSR on agriculture-related enterprises' exports. The results show that HSR can promote export growth of agriculture-related enterprises by 6.9%, and it will reach 10% in 5 years. However, the effect of HSR on the export of agriculture-related enterprises only exists within 45 km around HSR stations. HSR can reduce information barriers and costs for enterprises to enter the international market by providing transportation convenience and improving market access levels. HSR also offers local areas more transportation advantage compared to other surrounding areas, which in turn makes a siphon effect on export activities. Both these mechanisms are significant within 45 km, and it is extremely obvious for poor transportation areas and enterprises with higher productivity, and the siphon effect is even stronger than market access. Heterogeneity analysis results demonstrate that HSR has different effects for different types of enterprises.